Diodo emissor de luz na aclimatação de mudas de cana-de- açúcar em ambiente protegido - ALMEIDA NETO, Luiz Antônio de (2018)
Sugarcane is one of the main products of Brazilian agriculture. Due to its socioeconomic importance, it becomes increasingly important to understand the influence of environmental variables in its development, as well as the interaction of such variables with new technological approaches. The aim of this research was to evaluate the effect of the quality of supplementary artificial lighting, the light-emitting diode base (LED), in the acclimation of pre-sprouted sugarcane seedlings under greenhouse conditions and its performance in the field. The research was carried out in two stages, the first performed in a greenhouse located in the experimental area of the Federal Rural University of Pernambuco (UFRPE). The experimental design was completely randomized, composed of three supplementary lighting LED systems, in which the proportion of light was 90% Red + 10% Blue (R:B 90/10), 80% Red + 20% Blue (R:B 80/20), 70% Red + 30% Blue (R:B 70/30), and control, with natural solar radiation, with 5 replicates. For micrometeorological characterizing inside the greenhouse and in the external environment, sensors connected to a data logging automatic platform were installed, where air temperature (Ta, oC), relative humidity (UR, %), global solar radiation (Rg, MJ m-2 day-1 and W m-2), and photosynthetically active radiation (RFA, MJ m-2 day-1 and W m-2) were measured. The spectrum of solar radiation inside the greenhouse was obtained with a spectrometer. The evaluation of seedling growth of was performed through biometric indicators: plant height (AP, cm); stem length (CC, cm); stem diameter (DC, cm); leaf number (NF); leaf width and length (LF and CF, cm), root length (CR, cm), leaf area (AF, cm2), root volume (VR, mm3), shoot dry mass (MSPA, g) and root dry mass (MSR, g). The second stage was performed at the Estação Experimental de Cana-de-açúcar do Carpina (EECAC-UFRPE). The experimental plots were composed of pre-sprouted seedlings acclimatized in a greenhouse, exposed to the supplementary lighting systems. The experimental design was randomized blocks with 5 replicates. Plant growth evalution in the field followed the measurement of some biometric indicators: plant height (AP, cm); stem length (CC, cm); stem diameter (DC, mm) and tillers number (NP). It was found that the different LED systems promoted an increase in the PAR; however, until 20 days after planting supplementary lighting systems had little influence on the seedlings growth. At the end of the period of acclimatization, sugarcane seedlings subjected to the lighting system R:B 80/20 showed a greater association with the growth and size of seedlings. The biometric indicators obtained in the second stage of the research showed no significant differences, though plants under lighting systems with a greater proportion of the red wavelength (R:B 80/20 and R:B 90/10) were larger and presented a higher percentage of survival in the field.